Recent developments on computer aided fixture design: Case based reasoning approaches - Hashemi, H.; Mohamed Shaharoun, A.; Izman, S.; Kurniawan, Denni (2014)
Fixture design is an important issue in the process of manufacturing. As a critical design activity process, automation in fixture design plays an integral role in linking computer aided designs and computer aided manufacturing. This paper carries out a literature review of computer aided fixture design (CAFD) developments using intelligent methods that have been commonly utilized in automation in the last two decades. The first part of this review considers the steps of fixture design along with the significant researches and requirements of fixtures over time. After that, the paper presents important and relevant research carried out in the field of CAFD using intelligent approaches and the working principles surrounding this issue. The following section concentrates on the details of case based reasoning (CBR) approach, the most successful approach in CAFD. The examination of this approach is carried out based on applications, stages of CBR based systems fixture design, working principles, and pertinent proposed approaches. Lastly, the present drawbacks of the current methods and shortfalls in research are identified for future studies. © 2014 Heidar Hashemi et al.